Nexus Between Immune Responses and Oxidative Stress: The Role of Dietary Hydrolyzed Lignin in ex vivo Bovine Peripheral Blood Mononuclear Cell Response - Ciliberti, Maria Giovanna; Albenzio, Marzia; De Palo, Pasquale; Santillo, Antonella; Caroprese, Mariangela (Frontiers in Veterinary Science, 2020)
The control of immune responses is particularly critical when an increase of oxidative stress occurs, causing an impairment of immune cell response and a condition of systemic inflammation, named oxinflammation. Nutritional strategies based on the use in the diet of phytochemicals extracted from plants, and rich in antioxidants, could help in restoring the antioxidant/oxidant balance and obtaining a modulation of immune response. Lignin represents a valuable resource of phenolic compounds, which are characterized by a corroborated antioxidant effect. To date, there are no studies reporting the effects of lignin in the diet on immune responses and oxidative stress in ruminants. The objective of the present experiment was the evaluation of the dietary inclusion of Pinus taeda hydrolyzed lignin on the ex-vivo immune responses and oxidative stress biomarkers by peripheral blood mononuclear cells (PBMCs) isolated from beef steers. In order to test the effect during oxidative stress exposition, cells were treated with peroxide hydroxide (H2O2). The proliferation test and the viability assay were carried out on cells; whereas, on supernatants, the cytokine profile and the oxidative stress biomarkers were evaluated. The dietary inclusion with Pinus taeda hydrolyzed lignin resulted cytoprotective after H2O2 exposition, increasing the number of viable monocytes and decreasing the reactive oxygen/nitrogen species production in supernatants. The cytokine profile indicated the modulatory role of hydrolyzed lignin on immune response, with a concomitant decrease of TNF-α and increase of IL-8 production, which are strictly connected with monocyte activation and antioxidant response pathway. These results demonstrated that hydrolyzed lignin may provide a modulation of oxidative stress and inflammatory response in PBMCs; thus, the Pinus taeda hydrolyzed lignin could be suggested as innovative phytochemical in ruminant feed.